Proposta de uma estrutura de análise combinada da competitividade e sustentabilidade de cidades - Soares, Eduardo Codevilla (2013)
Because of globalization and increasing competitiveness, cities have sought to identify and evaluate the factors related to their performance and their impact on their development. Why are many factors that affect the competitive performance of cities, which today compete globally, it is extremely important that the analysis of competitiveness is treated systemically, thus enabling demonstrate the influence of economic, social and environmental their competitiveness. The present study aimed to analyze jointly the main factors of competitiveness and sustainability in the context of cities, considering the perception of social actors and experts. Based on the literature, were identified where different concepts and approaches to competitiveness and sustainability, drew up a proposal for the structure analysis of the categories of competitiveness that encompassed elements of sustainability. That proposal was later used as a research tool, to verify the applicability of the same in the perception of social actors and experts. Interviews were conducted and developed cognitive maps with twelve experts and social actors from nine different cities. Finally, the results obtained were analyzed and it was found that the structure proposed analysis is suitable to cities studied. The vast majority of the categories addressed in the structure analysis was cited by interviewees including categories such as those affecting the competitiveness and sustainability of their cities. It was found that sustainability can be a way to make cities more competitive for longer and it was found that respondents were able to identify the relationships and degrees of influence between the categories of competitiveness and sustainability. This allows us to conclude preliminarily that a city could be both competitive and sustainable, as well as factors discussed in both themes are complementary and not competitors, which identifies that the analysis of the competitiveness of a city should include sustainability factors.